Building Relevance Brick by Brick: The Practice of Newness - Elmér,Ella; Skøtt,Emil (2025)
Corporate brands face a persistent paradox of staying relevant and exciting in dynamic markets while maintaining consistency with their core identity. This thesis explores how corporate brands navigate this tension, referred to as the corporate brand paradox, by examining newness as a practice. While existing literature recognises newness as a vital element for enabling successful change, it primarily conceptualises it as a feature, capability, process, or event. However, these perspectives offer limited insights into how newness is enacted in practice. This study argues that identifying the everyday activities that constitute the practice of newness is crucial to understand how continuity and change can coexist in brand management. Conducting a qualitative single-case study of LEGO through interviews with employees across five departments, the study investigates the activities through which newness is practised in LEGO’s strategic brand management. The thematic analysis identifies four organising elements of newness as a practice: problem-solving capabilities, integrity-bound decision-making, future-oriented goals, and shared cultural understanding. The findings illustrate that newness is a routinised, strategic practice embedded in everyday brand management. The study contributed to branding literature by offering a practice-based perspective on newness and how this is used to navigate the paradox between continuity and change. Additionally, it offers practical implications for how brands can sustain long-term relevance without compromising their identity.
Keywords: Newness; practice theory; corporate brand paradox; continuity; change; relevance; strategic brand management